The Need for Enhancement of Teachers’ Pedagogical Skills for the Achievement of Quality Education in Private Schools in Sokoto State Nigeria - Abubakar, Usman (Eduscape : Journal of Education Insight, 2024)
This paper explores the challenges faced by private school teachers in Sokoto State, Nigeria, and advocates for targeted interventions to enhance pedagogical skills. The complexities of the modern educational landscape, coupled with unique challenges faced by private schools, necessitate a comprehensive approach to pedagogical skills enhancement. Examining the context of private schools in Sokoto State, the paper underscores the need for pedagogical excellence and its profound implications for student outcomes, classroom dynamics, and overall educational development. It argues that private schools, often prioritizing academic excellence, benefit from teachers equipped with diverse and effective instructional strategies. However, the study identifies significant challenges faced by private school teachers in Sokoto State. These challenges include restricted access to professional development, outdated teaching methodologies, insufficient support systems, inadequate compensation, diverse student populations, and limited access to technology. Each challenge is discussed in detail, highlighting its impact on the overall quality of education. In conclusion, the paper calls for a concerted effort to address these challenges and enhance pedagogical skills. It suggests evidence-based solutions, such as online platforms for professional development, comprehensive teacher training programs, mentorship initiatives, compensation and recognition programs, training for inclusive education, and exploring opportunities for technology access. The study concludes by emphasizing the transformative potential of investing in the professional development of private school teachers to realize quality education and holistic student development in Sokoto State.